The Effect of Linguistic Barriers to Business Entrepreneurship: The Case of Eldoret Town - Toboso , Bernard Mahero (African Journal of Education,Science and Technology (AJEST), 2014)
Small and medium business enterprises are an important sector of Kenya‟s economy. Millions of Kenyans depend on small scale businesses for their livelihood. This means that this sector is a source of employment to millions of people across the country. In a multilingual setting as is the case in Kenya, cross community communication can be a challenge. This means that cross community business undertakings can face challenges arising from language if linguistic issues are not addressed. Kenya has two official languages: English and Kiswahili. Although this is the case, not all Kenyans speak these two languages. This does not mean that Kenyans who do not understand these languages can not engage in business. It does not also mean that Kenyans who have little or no understanding of these languages of wider communication cannot seek goods and services in shops. However, for such people to engage in business and the acquisition of goods and services, they have to use alternative languages in their communication. In many cases, such people turn to their mother tongues as preferred languages of communication. However, in regions with high linguistic diversity, they are likely to encounter language barriers in their business interaction. As a result, traders and their customers employ various linguistic strategies to try and eliminate the strategies. This paper unravels linguistic barriers to business communication in Eldoret town and linguistic strategies employed by traders and their customers in the town in their effort to counter the challenges. The paper is based on research carried out in selected businesses within Eldoret town in Kenya